A evasão na educação de jovens e adultos: um estudo de caso da Escola Estadual Padre José de Anchieta/ Serra do Mel – RN - Lima, Ângela Aparecida de Almeida (Universidade Federal Rural do Semi-Árido, 2019)
Studying the history of Youth and Adult Education (EJA) is important because it allows a reflection on the entire historical process of this modality, as well as its current situation. Within this context is the great problem surrounding this type of education: dropout. We did a study at Padre José de Anchieta State School, located in Serra do Mel / RN, where we set out to reflect on the causes that lead students to evade the classroom. As a methodological procedure based on this work, interviews were conducted with students with four students and research school manager and this allowed us to have necessary knowledge for the diagnosis of this theme. The study of theorists, such as: Arroyo (2005), Freire (2002), Nóvoa (1992), Ramalho (2010), among others, was essential for us to have a deeper knowledge of our subject. The results after analysis of the interviews showed that many male students evade school early to work, in the case of women, marriage and children become obstacles to pursue their studies. In contrast, many learners return to school with the awareness that education can be their ally for a better future.
Monografia
Keywords: EJA; Evasão; Qualidade; Ensino; EJA; Evasion; Quality; Teaching; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL